Autoregressive Integrated Moving Average Untuk Memprediksi Kebutuhan Daya Listrik Kabupaten Lumajang - Fery Agung Prastyo; Moh Ahsan; Danang Aditya Nugraha (J I M P - Jurnal Informatika Merdeka Pasuruan, 2021)
The electricity consumption of PLN in Lumajang Regency consists of several types of customers including external customers, internal customers and intermediate customers. Prediction or forecasting in research to forecast the electricity consumption of each type of customer uses the Autoregressive Integrated Moving Average (ARIMA) technique. The research was carried out with data collection, data analysis using Autoregressive Integrated Moving Average. The results of forcasting with the ARIMA technique are based on the results of the smallest MSE and MAPE values. The results of the parameter significance test using the ARIMA model (1,1,0) obtained MSE 23236091976 and MAPE 5.52278%, while for the ARIMA model (0,1,1) MSE 24588319865 and MAPE 6.0376302% and for the ARIMA model (1,1 ,1) obtained MSE 139049864555 and MAPE 14.021832% so that it can be concluded that the ARIMA parameter model (1,1,0).Keyword — Forcasting, ARIMA, electric power, PLN Lumajang Regency